Effect of Plant Media Composition and POC Doses of Rabbit Urine on Growth and Yield of Melon (Cucumis melo L.) Plants - Lestari, Gita Ayu; Sumarsono; Fuskhah, Eny uskhah (Jurnal Online Pertanian Tropik, 2019)
Melon has a high economic value but in its cultivation, this plant requires quite an intensive handling. One effort to increase the production of melon plants is modifying planting media composition and fertilizing. This research aimed to examine the interaction between plant media composition and the rabbit urine fertilizer dosage on melon growth and yield. The research was held on April 4 to August 4, 2019, at The Agro Fruit Purwosari Greenhouse, Mijen, Semarang and Ecology, and Crop Production Laboratory, Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang. The study used a completely randomized factorial design 3x5 with 5 replications. The first factor was the growing media composition of 100% husk charcoal (M1), 75% husk charcoal + 25% soil (M2), 50% husk charcoal + 50% soil (M3). The second factor was rabbit urine fertilizer dosage of 55 ml/plant (P1), 82,5 ml/plant (P2), 110 ml/plant (P3), 137,5 ml/plant (P4), 165 ml/plant (P5). Data were analyzed by variance and proceeded with the DMRT test. The observed variables were plant height, amount of leaves, harvest age, fruit weight, fruit diameter, fruit sweetness level, crown, and root fresh weight, crown and root dry weight. The results of the study showed that the interaction of the growing media composition and rabbit urine fertilizer dosage was significant (P<0.05) on the parameters of plant height, amount of leaves, and fruit sweetness level. The treatment of (M2) obtained the highest result on the parameters of plant height, amount of leaves, and fruit sweetness level but had not been shown on the parameters of harvest age, fruit weight, fruit diameter, crown and root fresh weight, crown, and root dry weight.